LITERASI SOSIAL BUDAYA SEBAGAI PILAR MODERASI BERAGAMA DALAM PENDIDIKAN ISLAM KONTEMPORER - Agusta, Erna Sari; Arniady, Wisnu (Jurnal Lingkar Mutu Pendidikan, 2025)
In an increasingly pluralistic and global society, Islamic education is faced with the challenge of teaching the values of moderation, tolerance, and togetherness. Socio-cultural literacy, which includes a deep understanding of cultural diversity, history, and social norms, is an important foundation in strengthening moderate religious attitudes. This article analyzes how socio-cultural literacy can be integrated into the Islamic education curriculum through teaching that emphasizes openness to differences, strengthening cultural identity without losing the essence of religious values, and the formation of critical and inclusive thinking patterns. This study uses a research method with a case study approach where data is obtained through observation, interviews, and other data sources. The purpose of this study is to make strengthening socio-cultural literacy a pillar of religious moderation in Islamic education today. The results of the study show that socio-cultural literacy not only helps students understand the social and cultural context around them but also encourages the formation of moderate attitudes that are essential in creating social harmony in a multicultural society. Therefore, socio-cultural literacy must be an integral component in Islamic education in order to create a generation that is broad-minded, tolerant, and able to face the challenges of diversity with a moderate approach.